Silencing of Non-POU-domain-containing octamer-binding protein stabilizes atherosclerotic plaque in apolipoprotein E-knockout mice via NF-κB signaling pathway. (15th July 2018) - Zhang, Kai; Zhang, Fang; Yang, Jian-Min; Kong, Jing; Meng, Xiao; Zhang, Meng; Zhang, Cheng; Zhang, Yun
Abstract: Background: It remains unknown whether Non-POU-domain-containing octamer-binding protein (NonO) plays a causative role in plaque destabilization. We hypothesized that NonO gene silencing may stabilize atherosclerotic plaque by increasing P4Hα1 expression and inhibiting the inflammation. Methods and results: Vulnerable atherosclerotic plaques were induced in ApoE−/− mice by high fat diet, perivascular collar placement and mental stress. Compared with normal carotid arteries, those contained vulnerable plaques had high NonO expression. In another in vivo experiment, mice contained vulnerable plaques were randomly divided into 5 groups to receive physiological saline, si-N.C-lentivirus (LV), si-NonO-LV, pGC-GFP-LV and NonO-LV, respectively. NonO overexpression increased while NonO silencing decreased the incidence of carotid plaque disruption. NonO overexpression enhanced macrophage infiltration and lipid deposition but reduced the content of vascular smooth muscle cells and collagen in plaques, leading to an increased plaque vulnerability index, whereas NonO silencing exhibited the opposite effect. In addition, NonO overexpression increased the expression of proinflammatory cytokines and matrix metalloproteinases and decreased the expression of P4Hα1 both in vivo and in vitro, whereas NonO silencing showed the contrary effect. NonO co-immunoprecipitated with NF-κB p65, and promoted its nuclear translocation and phosphorylation, and these effects were reversed by NonO silencing. Conclusion: NonO may promote plaque destabilization and increase the incidence of plaque disruption in ApoE−/− mice by inducing the expression of inflammatory cytokines and matrix metalloproteinases and suppressing that of P4Hα1. The mechanism may involve the interaction of NonO with NF-κB leading to enhanced NF-κB nuclear translocation and phosphorylation. Highlights: NonO promoted plaque destabilization and increased plaque disruption incidence. NonO increased the expression of inflammatory cytokines and MMPs. The interaction of NonO and NF-κB maybe the mechanism of NonO's effect on plaque instability.